Screening of significant media components for production of bioprotein from coconut dregs using statistical approach - Hafiza, Shukor; Ahmad Anas, Nagoor Gunny; Nor Hidayah, B. (Universiti Putra Malaysia (UPM), 2012)
Link to publisher homepage at http://www.food.upm.edu.my/